Desire of the theater in the politician, desire of the politician in the theater and politician theater of desire (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The game of words that mobilizes the terms Theater, Desire and Politician, proposes a reflection in the field of theory and practice, of the text and scene, through three formulations - desire of the theater in the politician, desire of the politician in the theater and politician. theater of desire - opening a conversation with Guénoun (2003), Rancière (2012) and Benjamin (1994), respectively, to think about the modes of production and creation of the group Xama Teatro (Brasil - MA).
Keywords: Theater; Desire; Politician; Xama Theater; Northeast